2017
DOI: 10.1523/jneurosci.0846-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

How Auditory Experience Differentially Influences the Function of Left and Right Superior Temporal Cortices

Abstract: To investigate how hearing status, sign language experience, and task demands influence functional responses in the human superior temporal cortices (STC) we collected fMRI data from deaf and hearing participants (male and female), who either acquired sign language early or late in life. Our stimuli in all tasks were pictures of objects. We varied the linguistic and visuospatial processing demands in three different tasks that involved decisions about (1) the sublexical (phonological) structure of the British … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 58 publications
3
37
2
1
Order By: Relevance
“…A regression analysis revealed that greater dB loss was associated with greater activation in left STG auditory cortex, but no behavioral measures or demographic variables were linked to neural activation in right STG. This pattern is consistent with a recent fMRI study with congenitally deaf signers by Twomey et al (2017). These authors found that activation in left STG was sensitive to linguistic task demands, but activation in right STG was task-independent; no activation in STG (left or right) was observed for hearing signers performing the same tasks.…”
Section: <1> Sentence Readingsupporting
confidence: 91%
“…A regression analysis revealed that greater dB loss was associated with greater activation in left STG auditory cortex, but no behavioral measures or demographic variables were linked to neural activation in right STG. This pattern is consistent with a recent fMRI study with congenitally deaf signers by Twomey et al (2017). These authors found that activation in left STG was sensitive to linguistic task demands, but activation in right STG was task-independent; no activation in STG (left or right) was observed for hearing signers performing the same tasks.…”
Section: <1> Sentence Readingsupporting
confidence: 91%
“…Meanwhile, architectural and functional integrity of the temporal lobe is the first pass effect in speech rehabilitation . Any lesions involved in hearing loss, afferent stimulus interruption, or myelin hypoplasia, could eventually lead to a decreased volume or the inactivation of the auditory centre . There is little universal agreement on the plasticity of the auditory centre after hearing restoration.…”
Section: Discussionmentioning
confidence: 99%
“…20 Any lesions involved in hearing loss, afferent stimulus interruption, or myelin hypoplasia, could eventually lead to a decreased volume or the inactivation of the auditory centre. 21 There is little universal agreement on the plasticity of the auditory centre after hearing restoration. Our EEG source imaging results demonstrated that in prelingually deaf children, the auditory area, like the supra-temporal lobe, was able to be activated pCI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous behavioural studies in deaf children have shown that language deprivation, and not deafness per se , negatively impacts EF (Kalback, 2004; Figueras et al, 2008; Remine et al, 2008; Marshall et al, 2015; Botting et al, 2017). It is also known that late language acquisition can impact the reorganisation of auditory areas and the neural substrates of language processing (Neville and Bavelier, 1998; MacSweeney et al, 2008a,b; Mayberry et al, 2011; Cardin et al, 2013; Ferjan Ramirez et al, 2014, 2016; Cardin et al, 2016; Twomey et al, 2017), but it is not known what effect it has on neural executive processing. Revealing the effect of language experience on executive processing in the brain will provide unique insights into the nature and mechanisms of this relationship.…”
Section: Introductionmentioning
confidence: 99%